Defining Key Genes Regulating Morphogenesis of Apocrine Sweat Gland in Sheepskin - Li, Shaomei; Zheng, Xinting; Nie, Yangfan; Chen, Wenshuo; Liu, Zhiwei; Tao, Yingfeng; Hu, Xuewen; Hu, Yong; Qiao, Haisheng; Qi, Quanqing; Pei, Quanbang; Cai, Danzhuoma; et al. (Frontiers in Genetics, 2019)
Apocrine sweat gland is a unique skin appendage in humans comparing with mouse and chicken models. The absence of apocrine sweat glands in chicken and murine skin largely restrains further understanding of the complexity of human skin biology and skin diseases, like hircismus. Sheep may serve as an additional system for skin appendage investigation owing to the distributions and histological similarities of apocrine sweat glands in sheep trunk skin and human armpit skin. To understand the molecular mechanisms underlying morphogenesis of apocrine sweat gland in sheepskin, transcriptome analyses were conducted to reveal 1631 differentially expressed genes that were mainly enriched in three functional groups (cellular component, molecular function and biological process), particularly in gland, epithelial, hair follicle and skin development. There were 7 GO terms enriched in epithelial cell migration and morphogenesis of branching epithelium that were potentially correlated with the wool follicle peg elongation. Additional 5 GO terms were enriched in gland morphogenesis (20 genes), gland development (42 genes), salivary gland morphogenesis and development (8 genes), branching involved in salivary gland morphogenesis (6 genes) and mammary gland epithelial cell differentiation (4 genes). The enriched gland related genes and two KEGG pathway genes (WNT and TGF-β) were potentially involved in the induction of apocrine sweat gland. Genes named BMPR1A, BMP7, SMAD4, TGFB3, WIF1 and WNT10B were selected to validate transcript expression by qRT-PCR. Immunohistochemistry was performed to localize markers for hair follicle (SOX2), skin fibroblast (PDGFRB), stem cells (SOX9) and BMP signaling (SMAD5) in sheep skin. SOX2 and PDGFRB were absent in apocrine sweat glands. SOX9 and SMAD5 were both observed in precursor cells of apocrine sweat glands and later in gland ducts. These results combined with the upregulation of BMP signaling genes indicate that apocrine sweat glands were originated from outer root sheath of primary wool follicle and positively regulated by BMP signaling. This report established the primary network regulating early development of apocrine sweat glands in sheepskin and will facilitate the further understanding of histology and pathology of apocrine sweat glands in human and companion fur animal skin.